The New World screwworm in Mexico and Central America - Vargas Teran, M.
(Fr, Es)
Ilus., 8 ref.
Keywords: GANADO BOVINO; COCHLIOMYIA HOMINIVORAX; CONTROL DE PLAGAS; LIBERACION DE INSECTOS ESTERILES; SANIDAD ANIMAL; MEXICO; AMERICA CENTRAL; REVISTA MUNDIAL DE ZOOTECNIA